Analisis Empiris Pengaruh Impor dan Utang Luar Negeri terhadap Cadangan Devisa Indikator Stabilitas Eksternal - Wulan Dwi Lestari; Julita; Nadia Aprilia Agatha; Neli Aida; Muhammad Mufti Hudani; Qurota Ayu Nindya6 (CV. ITTC INDONESIA, 2025)
This study aims to empirically analyze the effect of imports and external debt on foreign exchange reserves as an indicator of external stability in Indonesia. External stability is a critical component in maintaining national economic resilience, reflected by the adequacy of foreign exchange reserves. The study employs a quantitative approach using the Ordinary Least Squares (OLS) method, utilizing annual data from 2009 to 2018. The independent variables consist of import values and external debt, while the dependent variable is foreign exchange reserves. The estimation results reveal that imports have a negative and statistically significant effect on foreign exchange reserves, whereas external debt has a positive but statistically insignificant effect. These findings suggest that rising import activity tends to deplete foreign exchange reserves, while external debt has not yet demonstrated a substantial contribution to reserve accumulation in the short term. Thus, a balanced management of imports and external debt is essential to support Indonesia's external stability. The study offers relevant policy implications for fiscal and monetary authorities in formulating sustainable macroeconomic strategies.